Blood Plasma Biomarkers for Woody Breast Disease in Commercial Broilers - Kong, Byungwhi; Khatri, Bhuwan; Kang, Seong; Shouse, Stephanie; Kadhim, Hakeem; Kidd, Michael; Lassiter, Kentu; Hiltz, Joseph; Mallmann, Barbara; Orlowski, Sara; Anthony, Nicholas; Bottje, Walter; et al. (Frontiers in Physiology, 2021)
Woody breast myopathy (WB) results in poor muscle quality. The increasing incidence of WB over the last several years indicates a need for improved prediction or early diagnosis. We hypothesized that the use of body fluids, including blood, may be more suitable than breast muscle tissue in developing a minimally invasive diagnostic tool for WB detection. To identify potential early-age-biomarkers that may represent the potential onset of WB, blood samples were collected from 100, 4 wk old commercial male broilers. At 8 wks of age, WB conditions were scored by manual palpation. A total of 32 blood plasma samples (8 for each group of WB and non-WB control birds at 2 time points, 4 wks and 8 wks) were subjected to shotgun proteomics and untargeted metabolomics to identify differentially abundant plasma proteins and metabolites in WB broilers compared to non-WB control (Con) broilers. From the proteomics assay, 25 and 16 plasma proteins were differentially abundant (p value <0.05) in the 4 and 8 wk old samples, respectively, in WB compared with Con broilers. Of those, FRA10A associated CGG repeat 1 (FRAG10AC1) showed the greater than 2 fold higher abundance in WB compared with Con broilers. In the 8 wk old broilers, 4 and 12 plasma proteins displayed higher and lower abundances, respectively, in WB compared with Con broilers. Myosin heavy chain 9 (MYH9) and lipopolysaccharide binding protein (LBP) showed more than 2 fold higher abundances in WB compared with Con broilers, while transferrin (TF) and complement C1s (C1S) showed more than 2 fold lower abundances compared with Con broilers. From the untargeted metabolomics assay, 33 and 19 plasma metabolites were differentially abundant in birds at 4 and 8 wks of age, respectively, in WB compared with Con broilers. In 4 wk old broilers, plasma 3-hydroxybutyric acid (3-HB) and raffinose concentrations showed the highest and lowest fold changes, respectively, in WB compared with Con broilers. The blood plasma 3-HB and raffinose concentrations were confirmed with targeted biochemical assays. Blood biomarkers, such as 3-HB and raffinose, may be suitable candidate targets in the prediction of WB onset at early ages.